Trend in Art Studies Post SWOT Analysis - Setyo Budi; Deny Tri Ardianto (Institut Seni Indonesia Denpasar, 2022)
Historical pieces of Indonesian Fine Arts show that art was once used as a provocative medium for political interests. This condition occurred when people only positioned art inthe factual aesthetic area without being balanced with conceptual intelligence. In the early 21st century, there was a revival of art discourse. Art-based higher education institutionsbegan to study arts in a balanced portion. This policy-oriented qualitative research produced a historiographical map of Indonesian art position, clarified by some changes in various policies in the academic environment. The era of 'National intelligenceawakening' is marked by visionary openness in the Higher Education environment. Such phenomenon demands adaptation and acceleration from the technical to strategic levels. The acceleration of educational technology eliminates various models of positivistic monitoring and evaluation. The use of SWOT Analysis in art fields should also be reviewed. The SDCS (Superiority, Differentiations, Connectedness, and Sustainability) analysis model offers a more visionary analysis in building the awareness that all higher education bodies in Indonesia should be “one giant educational mechanism” under one vision of improving the national intellect.